Corporate borrowing: currency denomination, debt maturity and institutional quality: evidence from emerging markets - Said, Yasmeen Hany (2018)
This thesis consists of 3 empirical papers examining the capital structure and debt maturity determinants from a developing economy perspective. Chapters 1 and 2 focus on firm-level determinants of local currency and foreign currency borrowing in South Korea over the period 1990 - 2006, which includes the 1997-1998 Asian financial crisis. Chapter 3 conducts a cross-country analysis using a dataset from the Middle East and Africa region (MEA hereafter) to study the firm level and institutional environment effects on debt maturity choices.